The effects of intercooling and regeneration on the thermo-ecological performance analysis of an irreversible-closed Brayton heat engine with variable-temperature thermal reservoirs - Sogut, Oguz Salim; Ust, Yasin; Sahin, Bahri (IOP PUBLISHING LTD, 2006)
A thermo-ecological performance analysis of an irreversible intercooled and regenerated closed Brayton heat engine exchanging heat with variable-temperature thermal reservoirs is presented. The effects of intercooling and regeneration are given special emphasis and investigated in detail. A comparative performance analysis considering the objective functions of an ecological coefficient of performance, an ecological function proposed by Angulo-Brown and power output is also carried out. The results indicate that the optimal total isentropic temperature ratio and intercooling isentropic temperature ratio at the maximum ecological coefficient of performance conditions (ECOPmax) are always less than those of at the maximum ecological function (E-max) and the maximum power output conditions (W-max) leading to a design that requires less investment cost. It is also concluded that a design at ECOPmax conditions has the advantage of higher thermal efficiency and a lesser entropy generation rate, but at the cost of a slight power loss.
Keywords: ENTROPY GENERATION MINIMIZATION; MAXIMUM POWER-DENSITY; OPTIMIZATION CRITERION; COEFFICIENT; CYCLE; THERMODYNAMICS; Physics